Integrasi Teknologi Informasi sebagai Sumber Belajar PAI untuk Meningkatkan Hasil Belajar Santri Pesantren - Ilyas, Muhammad; M. Afif Anshori; Sri Fatmawati (UNISAN JURNAL, 2025)
This study aims to analyze the integration of information technology as a learning resource in Islamic Religious Education (PAI) to improve students’ learning outcomes in Islamic boarding schools. The background of this research stems from the growing demand for digital technology utilization in education, including in pesantren, which are now adapting to modern learning demands. This study employed a descriptive qualitative approach with data collected through observation, interviews, and documentation. The findings reveal that the integration of information technology has positively influenced the PAI learning process, including increased learning motivation, broader access to learning materials, and greater student engagement. Students demonstrated significant improvement in cognitive understanding after using technology-based media such as instructional videos, digital applications, and online learning resources. Moreover, PAI teachers successfully utilized ICT to deliver learning materials more effectively and attractively. The study concludes that information technology contributes significantly to improving students’ learning outcomes, particularly in pesantren environments transitioning toward digital-based learning. Continued development of technology integration is recommended as part of sustainable PAI learning innovation.